Influence of Parenting Styles on Students’ Performance under Modular Distance Learning - Casinillo, Leomarich F; Agravante, Nicolle; Baldevia, Athena Claire N.; Tang, Erin Chanelle O. (Universitas Pendidikan Ganesha, 2023)
The influence of parents on their children is vital in that it molds a cognitive behavior that will reflect on their academic performance. During the COVID-19 pandemic, high school students have to learn in the form of modular learning in which they were just in their respective homes and their parents were taking the role of school teacher. This study aimed to evaluate the influence of different parenting styles of parents on the student's performance under modular distance learning amid the lockdown of the pandemic. Primary data were collected from 87 high school students who responded to the Google survey such as profiles of students, grades, and parenting styles using the Parental Authority Questionnaire (PAQ). The data gathered were analyzed through standard descriptive measures and correlational analysis. Results depicted that, on average, students have a